Management of fixed flexion contracture in primary total knee arthroplasty: recent systematic review - Sappey-Marinier Elliot; Fernandez Andréa; Shatrov Jobe; Batailler Cécile; Servien Elvire; Huten Denis; Lustig Sébastien (SICOT-J, 2024)
Introduction: This study aimed to systematically review the literature and identify the surgical management strategy for fixed flexion contracture in primary total knee arthroplasty (TKA) surgery, pre-, intra-, and post-operatively. Secondary endpoints were etiologies and factors favoring flexion contracture. Materials and methods: Searches were carried out in November 2023 in several databases (Pubmed, Scopus, Cochrane, and Google Scholar) using the following keywords: “flexion contracture AND TKA”, “fixed flexion deformity AND TKA”, “posterior capsular release AND TKA”, “posterior capsulotomy in TKA”, “distal femoral resection AND TKA”. Study quality was assessed using the STROBE checklist and the Downs and Black score. Data concerning factors or strategies leading to the development or prevention of flexion contracture after TKA were extracted from the text, figures, and tables of the included references. The effect of each predictive factor on flexion contracture after TKA was recorded. Results: Thirty-one studies were identified to meet the inclusion and exclusion criteria. These studies described a variety of preoperative and intraoperative factors that contribute to the development or correction of postoperative flexion contracture. The only clearly identified predictor of postoperative flexion contracture was preoperative flexion contracture. Intraoperative steps described to correct flexion contracture were: soft-tissue balancing (in posterior and medial compartments), distal femoral resection, flexion of the femoral component, and posterior condylar resection. However, no study has investigated these factors in a global model. Discussion: This review identified various pre-, intra-, and post-operative factors predictive of post-operative flexion contracture. In practice, these factors are likely to interact, and it is therefore crucial to further investigate them in a comprehensive model to develop an algorithm for the management of flexion contracture. Level of evidence: IV